Incidence of injury among adolescent soccer players: A comparative study of artificial and natural grass turfs - Aoki, H.; Kohno, T.; Fujiya, H.; Kato, H.; Yatabe, K.; Morikawa, T.; Seki, J. (Clinical Journal of Sport Medicine, 2010)
The article presents a study which aims to examine the incidence of acute injuries and chronic pain in soccer among adolescent players on training and matches with the use of natural grass turfs (NT) and artificial turfs (AT). The study found that AT group have greater incidence of low back pain on training and the relation of early adolescence and long training to chronic pain in AT group. Moreover, it suggests monitoring of adolescent players training on AT.